(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
Modern Chinese quantifiers are not only a unique system of Chinese parts of speech, but also differ in terms of usage due to differences in types, quantities, and other aspects. The Chinese people use a measure to represent anything or anything. This is one of the differences in language and culture compared to other countries. Famous Chinese linguist Guo Xianzhen mentioned in his 2002 work "Dictionary of the Usage of Quantifiers in Modern Chinese" that there are over 600 quantifiers used in different contexts in Chinese. Chinese noun quantifiers are often paired with nouns, while Chinese momentum words are often paired with verbs. For Chinese language learners, this unique nature becomes a challenge. So, let Chinese learners understand Chinese quantifiers, especially momentum words, and let them understand the usage of momentum words. For the convenience of learning, we searched and summarized the momentum words in the Chinese teacher training course of Mongolian National Education University to share with everyone. Хятад хэлний үйлийн тооллого үг ба сурах бичиг дэх тооллого үгийн судалгаа Хураангуй: Орчин цагийн хятад хэлний тооллого үг тухайн хэлний үгсийн аймгийн нэгэн онцлог бүхий тогтолцоо төдийгүй төрөл, тоо хэмжээнээс шалтгаалан хэрэглээний хувьд өөр өөр байдаг. Хятад ард түмэн аливаа юмс үзэгдлийг зайлшгүй хэм хэмжүүрээр илэрхийлж ирсэн нь бусад орны хэл, соёлоос ялгарах нэг онцлог болдог. Өөр өөр орчин нөхцөлд хэрэглэдэг 600-гаад төрлийн тооллого үг байдаг гэсэн судалгааг Хятадын нэрт эрдэмтэн, судлаач Гуо Шяньжэнь 2002 онд өөрийн бүтээлдээ дурдсан байдаг. Хятад хэлний нэрийн тооллого үг нь нэр үг, үйлийн тооллого үг нь үйл үгтэй хоршин хэрэглэгддэг энэхүү онцлог шинж чанар нь хятад хэл суралцагчдын хувьд томоохон бэрхшээл болдог учир тооллого үгийн тухай, ялангуяа үйлийн тооллого үг, хэрэглээний бүтэц, сурах бичиг дэх үйлийн тооллого үгийн судалгааг хураангуйлан та бүхэнд хүргэхийг зорилоо. Судалгааны үр дүнд МУБИС-ийн хятад хэлний мэргэжлийн ангид судалж буй анхан шатны сурах бичигт давтагдсан хэлбэрээр 4 үйлийн тооллого үг илэрч байхад дунд шатны сурах бичигт давтагдсан хэлбэрээр 16 үйлийн тооллого үг илэрч байна. Түлхүүр үг: хятад хэл, үйлийн нэгж үг, сурах бичиг, судалгаа